2013
DOI: 10.5993/ajhb.37.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time Associated with Health Behaviors and Outcomes in Adolescents

Abstract: Screen time was of significant importance to adolescent health. Behavioral interrelatedness caused significant confounding in the studied relations when behaviors were analyzed separately compared to a multi-behavioral approach, which speaks for more multi-behavioral analyses in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 39 publications
9
48
0
3
Order By: Relevance
“…Significant associations were not observed between screen time or computer use and physical self-concept in 1 study (Nihill et al 2013) and online gaming and self-esteem in another study (Kiraly et al 2014). Further, significant associations were only observed in females for 1 study (Busch et al 2013). Higher durations of cell phone use (2/2 studies) was associated with higher social self-esteem or self-concept (Jackson et al 2010(Jackson et al , 2011.…”
Section: Self-esteemmentioning
confidence: 87%
See 3 more Smart Citations
“…Significant associations were not observed between screen time or computer use and physical self-concept in 1 study (Nihill et al 2013) and online gaming and self-esteem in another study (Kiraly et al 2014). Further, significant associations were only observed in females for 1 study (Busch et al 2013). Higher durations of cell phone use (2/2 studies) was associated with higher social self-esteem or self-concept (Jackson et al 2010(Jackson et al , 2011.…”
Section: Self-esteemmentioning
confidence: 87%
“…The remaining 2 studies for TV viewing (Busch et al 2013;Rosen et al 2014), computer use (Busch et al 2013;Rosen et al 2014), and 1 study for video game use (Busch et al 2013) reported null findings. Similar to the longitudinal studies, associations were not significant across all measures of behavioural conduct/pro-social behaviour for 4 studies (Demirok et al 2012;Ferguson 2011;Ozmert et al 2011;Rosen et al 2014).…”
Section: S249 Published By Nrc Research Pressmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are also indications that specific types of screen time can have positive effects on social and mental outcomes 14 . Thus, in addition to understanding the impacts of different types of screen time, other knowledge gaps persist regarding the relationship between these exposures and mental health indicators, such as the gradual relation (dose-response), differences between sexes 15 , and cultural contexts 16 . In this sense, our aim was to analyze the association between screen time (TV, computer, and video-game), mental health, and social relationships in Brazilian adolescents.…”
Section: Introductionmentioning
confidence: 99%